NURR1 Alterations in Perinatal Stress: A First Step towards Late-Onset Diseases? A Narrative Review - Laura Bordoni; Irene Petracci; Jean Calleja-Agius; Joan G. Lalor; Rosita Gabbianelli (Biomedicines, 2020)
Perinatal life represents a delicate phase of development where stimuli of all sorts, coming to or from the mother, can influence the programming of the future baby’s health. These stimuli may have consequences that persist throughout adulthood. Nuclear receptor related 1 protein (NURR1), a transcription factor with a critical role in the development of the dopaminergic neurons in the midbrain, mediates the response to stressful environmental stimuli in the perinatal period. During pregnancy, low-grade inflammation triggered by maternal obesity, hyperinsulinemia or vaginal infections alters NURR1 expression in human gestational tissues. A similar scenario is triggered by exposure to neurotoxic compounds, which are associated with NURR1 epigenetic deregulation in the offspring, with potential intergenerational effects. Since these alterations have been associated with an increased risk of developing late-onset diseases in children, NURR1, alone, or in combination with other molecular markers, has been proposed as a new prognostic tool and a potential therapeutic target for several pathological conditions. This narrative review describes perinatal stress associated with NURR1 gene deregulation, which is proposed here as a mediator of late-onset consequences of early life events.